Efektivitas E-Government Pembayaran Pajak Kendaraan Bermotor Berbasis Aplikasi Bapenda Sulsel - Samudra, Nila Asri; Setiawati, Budi; Yahya, Muhammad (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2025)
Abstract The purpose of the study was to determine the Effectiveness of E-Government Motor Vehicle Tax Payments based on the Bapenda Sulsel Mobile Application at the Regional Revenue Agency of South Sulawesi Province. The type of research uses a qualitative method with a descriptive research type, data collection techniques through observation, interviews, and documentation. The results of the study indicate that the Effectiveness of Motor Vehicle Tax Payments based on the Bapenda Sulsel Mobile Application at the Regional Revenue Agency of South Sulawesi Province can be categorized as quite effective, because of the three indicators only one is not yet effective. Achievement of objectives in its implementation is efficient in terms of time and the realization of Motor Vehicle Tax growth has increased significantly which has contributed greatly to Regional Original Income. Integration carried out with several other agencies and various methods of socialization, namely direct socialization to the community. Adaptation in terms of human resources is not adequate, there is still a lack of human resources for the development of this application, but the infrastructure is adequate.